(النَّقْدُ عَلَى دَلِيْلِ إِقَامَةِ الخِلَافَةِ لِحِزْبِ التَّحْرِيْرِ إِنْدُوْنِيْسِيَا: تَحْلِيلُ الأَحَادِيْثِ فِي تَفْسِيْرِ الْقُرْآنِ الْعَظِيْمِ لِإِبْنِ أَبِيْ حَاتِمٍ (ت. 327 هـ - Asbiani, Abdurrahim; Muhammad Azizan Fitriana; Syamsul Ariyadi (ISLAM NUSANTARA:Journal for the Study of Islamic History and Culture, 2025)
This article discusses about criticism of the argument for establishing a caliphate for Hizbut Tahrir Indonesia (HTI) with analysis of hadith in the interpretation of bi ar-riwāyah. The Khilafah aims to enforce Islamic law. There are several groups or mass organizations that are trying to implement the caliphate. One group in Indonesia is Hizbut Tahrir Indonesia. They are of the opinion that any state system cannot be accepted or even called infidel if it is not based on the Koran and Hadith. There is a lot of research on the caliphate, such as discussing the caliphate historically, or referring to classical and contemporary tafsir books. Likewise with the discussion of takhrīj, quite a few studies discuss takhrīj or hadith analysis. In this study, researchers analyzed the hadiths in the tafsir bi ar-riwāyah or more precisely Tafsīr Al-Qur`Ān Al-‘Aẓīm by Ibn Abī Ḥātim. This research is limited to verses that are understood as arguments for upholding the concept of the caliphate, namely QS. Āli ‘Imrān [3]: 110, QS. al-Mā`idah [5]: 44 and QS. al-Mā`idah [5]: 48. This research is “Library Research” using qualitative methods. The approach used is the takhrīj hadith approach. In the analysis of takhrīj hadith, the author starts by bringing in hadith from other sources if there are other sources. Then the writer examines the narrators of the sanad (criticism of sanad) and explains the meaning of the hadith (syarh hadith) along with the law (quality) of the sanad. From this research, we can find out the source and quality of the hadiths as well as explanations of these hadiths, so that there is no mistake in understanding the hadith text. After research, there were several narrations (sanad) that were invalid because there were problematic narrators. Of the 8 historical texts, 5 of them have the quality of sanad daīf and the remaining 3 are ḥasan. Of the various words of the caliphate in the Koran, there is no word that discusses and requires the caliphate. Key words: Khilafah, Hizbut Tahrir Indonesia, Tafsir Ibn Abī Ḥātim.